If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -3x = 22 Solving 1 + -3x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 22 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 22 + -1 -3x = 22 + -1 Combine like terms: 22 + -1 = 21 -3x = 21 Divide each side by '-3'. x = -7 Simplifying x = -7
| 8=z/4=23 | | -36=-2A-9B+C | | -11-18-4w/5 | | 7(7+25)+(5+6)10= | | 2x-1+5+x=180 | | 8-1/7u5 | | 20+2y-5=9y-13-3y | | 26=4A+2B | | 3(4+25)-12+-15= | | -6x+20=4x-30 | | 18x+12y=165 | | (2a^-5b^4c^3)^-2/(3a^3b^-7c^3)^2 | | A^2-3a-45=0 | | A^2-3a-34=0 | | 3/8v3 | | x^2+4x-10= | | 10(x+3)=31 | | 111-4u/3 | | 180*(n-2)=1 | | 6sin^2x+9sinx+3=0 | | 5d=3m-14 | | -2v/7-10-15 | | y=7x+55 | | 3(y+-2)+-1=1 | | 6(y-1)=3y-15 | | 2*x+x^2+y^2+17=12*y | | 2x^2-10d-9=0 | | -6p=3(2p-3)-4(-10+4p) | | 3y+-6+-1=1 | | 138-1/7y | | 6x^3+28x^2+16x= | | 7(3y-5)+2(4y+3)= |